Correlations of Internet Addiction Severity With Reinforcement Sensitivity and Frustration Intolerance in Adolescents With Attention-Deficit/Hyperactivity Disorder: The Moderating Effect of Medications - Lu, Wei-Hsin; Chou, Wen-Jiun; Hsiao, Ray C.; Hu, Huei-Fan; Yen, Cheng-Fang (Frontiers in Psychiatry, 2019)
The aims of this study were (1) to examine the associations of internet addiction (IA) severity with reinforcement sensitivity and frustration intolerance and (2) identify the moderators of these associations among adolescents diagnosed with attention-deficit/hyperactivity disorder (ADHD) in Taiwan. A total of 300 adolescents aged between 11 and 18 years who had been diagnosed with ADHD participated in this study. Their levels of IA severity, reinforcement sensitivity, and frustration intolerance were assessed using the Chen Internet Addiction Scale, behavioral inhibition system (BIS) and behavioral approach system (BAS), and Frustration Discomfort Scale, respectively. The associations of IA severity with reinforcement sensitivity and frustration intolerance were examined using multiple regression analysis. The results found that higher fun seeking on the BAS (p = .003) and higher frustration intolerance (p = .003) were associated with more severe IA. Receiving medication for treating ADHD moderated the association between fun seeking on the BAS and IA severity. Fun seeking on the BAS and frustration intolerance should be considered as targets in prevention and intervention programs for IA among adolescents with ADHD.